THE IMPLEMENTATION OF VENTILATOR ASSOCIATED PNEUMONIA BUNDLE (VAP) IN THE ICU OF EKA HOSPITAL, PEKANBARU - Erna Maria; Vetty Yulianty Permanasari (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Nosocomial infections or known as Hospital Acquired Infections (HAIs) is a worldwide problem. VAP is nosocomial pneumonia which occurs more than 48 hours after installation of mechanical ventilation, either through an endotracheal tube or tracheostomy. The patient in ICU have high risk on VAP infection and increasing morbidity, mortality and also prolonged length of hospital stay Methods: This research is an observational study evaluating conditions before and after a specific standard operating procedure being implemented in reducing VAP infection in ICU EKA Hospital Pekanbaru. Results: It’s obtained from medical record data of 339 patients hospitalized at ICU of Eka Hospital Pekanbaru ranging from 2016 to 2017. There is significant decrease number of VAP infections in 2017 by 60%. The reduction occurred due to the application of a routine VAP Bundle covering 100% for all hospitalized ICU patients. Conclusions: Strict monitoring and supervision are required to maintain VAP bundle and reduce the incidence of VAP infection in ICU of Eka Hospital Pekanbaru.